Changes in physiological properties of rat ganglion cells during retinal degeneration - Sekirnjak, Chris (American Physiological Society, 2011)
Retinitis pigmentosa (RP) is a leading cause of degenerative vision loss, yet its progressive effects on visual signals transmitted from the retina to the brain are not well understood. The transgenic P23H rat is a valuable model of human autosomal dominant RP, exhibiting extensive similarities to the human disease pathology, time course, and electrophysiology. In this study, we examined the physiological effects of degeneration in retinal ganglion cells (RGCs) of P23H rats aged between P37 and P752, and compared them with data from wild-type control animals. The strength and the size of visual receptive fields of RGCs decreased rapidly with age in P23H retinas. Light responses mediated by rod photoreceptors declined earlier (∼P300) than cone-mediated light responses (∼P600). Responses of ON and OFF RGCs diminished at a similar rate. However, OFF cells exhibited hyperactivity during degeneration, whereas ON cells showed a decrease in firing rate. The application of synaptic blockers abolished about half of the elevated firing in OFF RGCs, indicating that the remodeled circuitry was not the only source of degeneration-induced hyperactivity. These results advance our understanding of the functional changes associated with retinal degeneration.